STUDENTS` PERCEPTION TOWARD ENGLISH CLUB TO SUPPORT SPEAKING SKILLS - Nawati, Agus; Elyza, Ferlya; Susiani, Rini (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This study aims to identity students` perception of English club to improve their speaking ability and to know about some activities provided by English club. The study involved 12 students from fifth semester in the English department and used mix methods. According to the results data analysis from the questionnaire distributed to 12 students of the fifth semester, it was found that students gave positive assessment of the English club to support their speaking skills. Questionnaire and interview used as instruments in this study, as presented by the questionnaire data with a strongly agree category (83,50%). The result of the interview data with five students from fifth semester also gave positive perception, the English club helped them practice speaking happily, build confidence and encourage critical thinking. The activities provided based on the results of interview data with the head of the English club are tourism, watching and reviewing short films, visiting historical places, playing games and listening to music. The results of this study show that English club support students` speaking skills